Counteracting Downstream Effects Using Turbulence Promoters in Retrofit - Jorge Luis García-Castillo; Martín Picón-Núñez; Jesús Alberto Crespo-Quintanilla (Chemical Engineering Transactions)
One of the simplest strategies for retrofitting heat recovery networks with the goal of reducing energy consumption in a process is the implementation of turbulence promoters. However, an adverse effect of this measure in heat recovery networks is the generation of downstream temperature disturbances that impact the operation of equipment within the network. This study introduces the use of Perforated Twisted Tapes (PTT) in retrofit schemes to enhance thermal load while simultaneously mitigating adverse effects related to network structure. General thermohydraulic correlations have been developed to analyse the implementation of twist ratios between 2 and 7. Through a case study with multiple scenarios, it has been observed that when using higher-density promoters (with a twist ratio of 2), energy savings are reduced by 38.38 % due to adverse effects, resulting in net savings of 3.66 MW. In the case of using promoters with lower density (with a TR=7), the reduction in savings is 26.67 %, with net savings of 3.52 MW.